2021
DOI: 10.3390/jcm10214828
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Enzyme Replacement Therapy in Late-Onset Pompe Disease

Abstract: Pompe disease (PD) is a glycogen storage disorder caused by deficient activity of acid alpha-glucosidase (GAA). We sought to review the latest available evidence on the safety and efficacy of recombinant human GAA enzyme replacement therapy (ERT) for late-onset PD (LOPD). Methods: We systematically searched the MEDLINE (via PubMed), Embase, and Cochrane databases for prospective clinical studies evaluating ERT for LOPD on pre-specified outcomes. A meta-analysis was also performed. Results: Of 1601 articles ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
(163 reference statements)
0
6
0
Order By: Relevance
“…in 50% of patients (Supplementary Figure S3), especially in those with longer disease duration. This improvement in motor response peaking 1-3 years after the start of ERT, followed by stabilization, is common to most studies (Anderson et al, 2014;Kuperus et al, 2017;Schoser et al, 2017), and confirmed by recent reviews (Dornelles et al, 2021;Sarah et al, 2021). A recent review (Berli et al, 2021) failed to detect significant changes in FVC, that remained stable during a follow-up ranging 6 months to 7 years in different studies.…”
Section: Main Motor and Respiratory Outcomes: 6mwt And Fvcmentioning
confidence: 64%
See 1 more Smart Citation
“…in 50% of patients (Supplementary Figure S3), especially in those with longer disease duration. This improvement in motor response peaking 1-3 years after the start of ERT, followed by stabilization, is common to most studies (Anderson et al, 2014;Kuperus et al, 2017;Schoser et al, 2017), and confirmed by recent reviews (Dornelles et al, 2021;Sarah et al, 2021). A recent review (Berli et al, 2021) failed to detect significant changes in FVC, that remained stable during a follow-up ranging 6 months to 7 years in different studies.…”
Section: Main Motor and Respiratory Outcomes: 6mwt And Fvcmentioning
confidence: 64%
“…Indeed, lack of quality of like measures is common to most reviewed studies (Schoser, Berli, Dornelles). In a very recent review (Dornelles et al, 2021), only 6 studies reported QL measures, and in all cases it was SF36; the changes observed were only in the physical domain, with substantial heterogeneity and very low certainty of evidence, suggesting that this scoring system may not be the best suitable measure for LOPD. Further outcomes are thus desirable, including scores more specific for LOPD or, at least, more specific to neuromuscular diseases, although evaluating a subjective measure in an open trial will remain, in my opinion, challenging: we see that, even when asked about subjective improvement, some patients (especially older patients) tend to report they are well, since they are aware of the costs of treatment and always fear the interruption of treatment if they admit a clinical worsening.…”
Section: Longitudinal Variations In Response and Definition Of Respondermentioning
confidence: 99%
“…Indeed, the effectiveness of this approach provides a compelling rationale for the inclusion of PKU in virtually all newborn screening panels. In the case of enzyme deficiencies, enzyme replacement therapy is another therapeutic strategy that has been successful (Brady, 1983; Dornelles et al, 2021). The main point is that the development of these drugs was dependent upon understanding the biochemical abnormalities in individual diseases, and for the most part represent the “one disease at a time” approach.…”
Section: Traditional Drug Development Versus Gene‐targeted Therapiesmentioning
confidence: 99%
“…88 ERT for Pompe disease has drastically improved the survival rates in affected individuals, [89][90][91][92][93] resulting in the emergence of new phenotypes, including variable central nervous system involvement in children with IOPD [94][95][96][97][98][99][100][101] and progression of disease in individuals with LOPD treated with ERT, including respiratory function and functional outcomes. 89,102,103 Furthermore, the addition of Pompe disease to newborn screening (NBS) programs in Taiwan in 2005 104 and the United States Recommended Uniform Screening Panel in 2015 has permitted early diagnosis of patients with IOPD, as well as those with LOPD who otherwise appear healthy. 105 Natural history of patients who are detected on NBS is continuing to evolve; studies in Taiwan and the United States are shedding light on the early involvement and a characteristic phenotype in infants and children with LOPD diagnosed via NBS.…”
Section: Gsd II (Pompe Disease)mentioning
confidence: 99%
“…Immunomodulation strategies have since been employed to induce immune tolerance to ERT in affected individuals who are cross‐reactive immunologic material (CRIM)‐negative and would otherwise develop an IgG antibody immune response to the ERT, leading to a deeper understanding of the natural history of CRIM‐negative individuals that otherwise would have succumbed to the disease despite ERT 88 . ERT for Pompe disease has drastically improved the survival rates in affected individuals, 89–93 resulting in the emergence of new phenotypes, including variable central nervous system involvement in children with IOPD 94–101 and progression of disease in individuals with LOPD treated with ERT, including respiratory function and functional outcomes 89,102,103 . Furthermore, the addition of Pompe disease to newborn screening (NBS) programs in Taiwan in 2005 104 and the United States Recommended Uniform Screening Panel in 2015 has permitted early diagnosis of patients with IOPD, as well as those with LOPD who otherwise appear healthy 105 .…”
Section: Natural History and Animal Models For The Gsdsmentioning
confidence: 99%